Ludicity Elements in Education of Teachers of Polish as a Foreign Language - Biernacka, Michalina; Kaźmierczak, Paulina; Banach, Agnieszka (Ludicity in (Glotto)Didactic, 2020)
The article aims at introduction of ludic elements in the process of teaching teachers of the Polish language to foreigners. The author shows examples of lessons conducted by using ludicity methods. The main topics of this lessons includes: pre-classes, internet in teacher’s work, lessons for children and youth, and the ability to adapt games for lessons of a foreign language. The article describes basic advantages and disadvantages of using ludicity methods at the university and proves that they are necessary elements of the didactic process.